Oleuropein Mitigates Acrylamide-Induced Nephrotoxicity by Affecting Placental Growth Factor Immunoactivity in the Rat Kidney - Kıymet Kübra Tüfekci; Musa Tatar (AVES YAYINCILIK A.Ş., 2023)
Oleuropein is one of the main components of the antioxidant properties of olive leaves. Placental growth factor is an important regulator in angiogenesis and inflammation, its levels being variable in pathological conditions. In this study, we aimed to examine changes in placental growth factor expression and the effect of oleuropein, found in olive leaves, in rats exposed to acrylamide nephrotoxicity.Twenty-four male Wistar albino rats were allocated into 4 groups. The control group received saline solution only. The oleuropein group received oleuropein (4.2 mg/kg), the acrylamide group received acrylamide (5 mg/kg), and the acrylamide and oleuropein group received acrylamide (5 mg/kg) and oleuropein (4.2 mg/kg). All substances were administered via gastric gavage for 21 days. Kidney tissues were removed at the end of the study and subjected to histopathological, stereological, and immunohistochemical procedures.Histopathological examination revealed dilatation, vacuolization, and degeneration in the proximal and distal tubules and increased placental growth factor immunoreactivity in the acrylamide group. Cavalieri volume analysis revealed increased cortex, distal, and proximal tubule volumes (P < .01).Oleuropein significantly attenuated acrylamide-induced kidney injury by altering placental growth factor immunoreactivity. Placental growth factor immunoreactivity can be used as a marker of acrylamide nephrotoxicity, and oleuropein may counteract acrylamide-induced kidney injury.
Keywords: Medicine (General); R5-920; Original Article; 3. Good health